Synthesis of Silica-Based Solid-Acid Catalyst Material as a Potential Osteochondral Repair Model In Vitro - Long, Rui-Min; Jiang, Yan; Guo, Jia-Qi; Ren, Gang; Guo, Xian-Xin; Xie, Xue; Wu, Yue; Yan, Rui-Da; Lin, Zi-Zhen; Wang, Shi-Bin; Liu, Yuan-Gang (Frontiers in Bioengineering and Biotechnology, 2021)
For osteochondral damage, the pH value change of the damaged site will influence the repair efficacy of the patient. For better understanding the mechanism of the acid-base effect, the construction of in vitro model is undoubtedly a simple and interesting work to evaluate the influence. Here, a novel porous silica-based solid-acid catalyst material was prepared by additive manufacturing technology, exhibiting improved eliminating effects of the residue. SEM, FTIR, and TGA were used to characterize the morphology, structure, and thermal stability of the synthesized 3D material. The reaction between 4-methoxybenzyl alcohol and 3, 4-dihydro-2H-pyran was used as a template reaction to evaluate the eliminating performance of the 3D porous material. Solvents were optimized, and three reaction groups in the presence of 3D SiO2, 3D SiO2-SO3H, and 3D SiO2-NH-SO3H, as well as one without catalyst, were compared. In addition, in consideration of the complicated situation of the physiological environment in vivo, universality of the synthesized 3D SiO2-NH-SO3H catalyst material was studied with different alcohols. The results showed that the sulfonic acid-grafted 3D material had excellent catalytic performance, achieving a yield over 95% in only 20 min. Besides, the catalyst material can be recycled at least 10 times, with yields still higher than 90%. Such a solid catalyst material is expected to have great potential in additive manufacturing because the material is easy-recyclable, renewable and biocompatible. The 3D catalyst material with connective channels may also be utilized as an in vitro model for environment evaluation of osteochondral repair in the future.